Seniority and Bullying Behavior in the Elderly in Nursing Homes - Kosapilawan, Mickhel Fernando Radiena; Adu, Apris A; Damayanti, Yeni (Universitas Nusa Cendana, 2025)
Bullying and seniority are phenomena that can be found across various social groups and age ranges. These behaviors occur not only among children or adolescents but also in daily interactions, including among the elderly. In nursing homes, for example, bullying persists despite the physical limitations that aging brings. This study aims to explore the impact and the underlying factors that contribute to seniority and bullying behaviors among older people. A qualitative approach was used, employing the photo-elicitation technique, with two participants who met the selection criteria. The results of the study indicate that seniority and bullying behaviors among older people are influenced by early character development, particularly by authoritarian parenting styles, as well as the social conditions that create bullying victims. The consequences of these behaviors include social sanctions, such as being ostracized from interaction with other residents.